2019
DOI: 10.1186/s13041-018-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapamycin on social interaction deficits and gene expression in mice exposed to valproic acid in utero

Abstract: The mammalian target of rapamycin (mTOR) signaling pathway plays a crucial role in cell metabolism, growth, and proliferation. The overactivation of mTOR has been implicated in the pathogenesis of syndromic autism spectrum disorder (ASD), such as tuberous sclerosis complex (TSC). Treatment with the mTOR inhibitor rapamycin improved social interaction deficits in mouse models of TSC. Prenatal exposure to valproic acid (VPA) increases the incidence of ASD. Rodent pups that are exposed to VPA in utero have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 62 publications
0
45
1
Order By: Relevance
“…Based on the DU-145 prostate cancer cell line, evidence has been presented that HDAC–mTOR cross-linking exists in the tumor cells, whereby elevation of aH3 and aH4 is coupled to reduced pmTOR and pRaptor, but also to an enhanced pRictor and pAkt expression level [11]. Accordingly, a microarray analysis in an animal model has shown that VPA exposure decreased the mTOR but increased the Akt gene [38]. VPA also promoted an increase in the Akt phosphorylation level in mice [39].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the DU-145 prostate cancer cell line, evidence has been presented that HDAC–mTOR cross-linking exists in the tumor cells, whereby elevation of aH3 and aH4 is coupled to reduced pmTOR and pRaptor, but also to an enhanced pRictor and pAkt expression level [11]. Accordingly, a microarray analysis in an animal model has shown that VPA exposure decreased the mTOR but increased the Akt gene [38]. VPA also promoted an increase in the Akt phosphorylation level in mice [39].…”
Section: Discussionmentioning
confidence: 99%
“…We considered this day as embryonic day 0.5 (E0.5). On E12.5, 600 mg/kg of valproic acid sodium salt (VPA; Sigma, St. Louis, MO, USA) dissolved in saline solution (VPA mice) or saline solution alone (as a control; Sal mice) was injected into the subcutaneous fat of the neck of pregnant mice 7,9,33,62,63 . A 3-chambered social-approach test was performed using male mice to confirm whether VPA mice were an appropriate model of ASD (Sal: n = 8 from 3 mothers; VPA: n = 10 from 4 mothers).…”
Section: Methodsmentioning
confidence: 99%
“…Kotajima-Murakami et al [35] treated prenatally VPA exposed pups with intraperitoneal injection of rapamycin for 2 consecutive days. The mammalian target of rapamycin (mTOR) signaling pathway plays a crucial role in cell growth, proliferation and metabolism.…”
Section: Introductionmentioning
confidence: 99%